Bank of Japan's Quantitative and Credit Easing : Are they Now More Effective - Fasano-Filho, Ugo (IMF Working Papers; Working Paper, 2012)
This paper asks whether the BoJ's recent experience with unconventional monetary easing has been effective in supporting economic activity and inflation. Using a structural VAR model, the paper finds some evidence that BoJ's monetary policy measures during 1998-2010 have had an impact on economic activity but less so on inflation. These results are stronger than those in earlier studies looking at the quantitative easing period up to 2006 and may reflect more effective credit channel as a result of improvements in the banking and corporate sectors. Nevertheless, the relative contribution of monetary policy measures to the variation in output and inflation is rather small.